Characterization of Exopolysaccharide producing Sinorhizobium Kostisense isolated from root nodules of Vigna Trilobata (Funded work) - G. KRANTHI KUMAR; M. RAGHU RAM (International Journal of Pharma and Bio Sciences, 2018)
Exopolysaccharide (EPS) of symbiotic bacteria is indispensable for the invasion of root that leads to formation of nodule in legume plant. In the present study 21 rhizobacterial strains were isolated from root nodules of Vigna trilobata plants raised in soils collected from geographically different areas in A.P. India. All the strains produced Exopolysaccharides in the presence of YEM broth. But copious amount of EPS (892 mg/100ml) was produced by Sinorhizobium kostisense MRR 104. The identification of bacteria was done by 16 S rDNA sequencing analysis. pH 7.0 and 37 0C temperature are optimum conditions for ideal production of Exopolysaccharides for this strain. FT-IR spectroscopy revealed the presence of functional groups that accounts for its overall structure and functional property. Fourier transformation infrared spectroscopy of exopolysaccharide indicated the presence of Hydroxyl, Carboxyl, Acetyl and Pyruvyl groups. Chemical analysis of EPS revealed that it is primarily composed of neutral sugars, uronic acids, and proteins. Exopolysaccharides showed good emulsification property and viscosity that indicated its possible use as an additive in food industry and also used as gelling agents.